Husband and wife do it together : sex - Du, Shanshan (American Antropological Association, 2000)
In this article, I explore both the diversity and commonality of human labor organization in response to sex difference through an ethnographic study of the sex/gender allocation of labor among the Qhawqhat Lahu of Lancang, China. I argue that the principle of "unity," rather than the more commonly discussed "division," predominantly governs the gendered allocation of labor in Qhawqhat. I demonstrate that the Lahu ideal of gender unity, combined with their practical pursuit of optimal use of household laborers, foster an extraordinarily high degree of joint gender roles in child rearing, as well as in reproductive and productive activities in general. I also show that such an extreme sociocultural system minimizes (although it does not entirely negate) the impact of sex differences. This study may shed some light on the diversity and commonality of human labor organization in response to sex difference by bringing into dialogue more recent approaches to the issue and earlier studies of the "sexual division of labor